Thermal analysis of metal-organic precursors for functional cu:Νiox hole transporting layer in inverted perovskite solar cells: Role of solution combustion chemistry in cu:Νiox thin films processing - Ioakeimidis, Apostolos; Papadas, Ioannis T.; Koutsouroubi, Eirini D.; Armatas, Gerasimos S.; Choulis, Stelios A. (My University, 2021)
Low temperature solution combustion synthesis emerges as a facile method for the synthesis of functional metal oxides thin films for electronic applications. We study the solution combustion synthesis process of Cu:NiOx using different molar ratios (w/o, 0.1 and 1.5) of fuel acety-lacetone (Acac) to oxidizer (Cu, Ni Nitrates) as a function of thermal annealing temperatures 150, 200, and 300 °C. The solution combustion synthesis process, in both thin films and bulk Cu:NiOx, is investigated. Thermal analysis studies using TGA and DTA reveal that the Cu:NiOx thin films show a more gradual mass loss while the bulk Cu:NiOx exhibits a distinct combustion process. The thin films can crystallize to Cu:NiOx at an annealing temperature of 300 °C, irrespective of the Acac/Ox-idizer ratio, whereas lower annealing temperatures (150 and 200 °C) produce amorphous materials. A detail characterization study of solution combustion synthesized Cu:NiOx, including XPS, UV-Vis, AFM, and Contact angle measurements, is presented. Finally, 50 nm Cu:NiOx thin films are introduced as HTLs within the inverted perovskite solar cell device architecture. The Cu:NiOx HTL annealed at 150 and 200 °C provided PVSCs with limited functionality, whereas efficient triple-cation Cs0.04(MA0.17FA0.83)0.96 Pb(I0.83Br0.17)3-based PVSCs achieved for Cu:NiOx HTLs for annealing temperature of 300 °C.
Keywords: Cu:NiOx; Metal oxides; Solution combustion synthesis; Metal-organic precursors; Fuels; Oxidizers; Electronic thin films; Hole transporting layers; Annealing temperature; Perovskite solar cells